Writing and registering instruments in NE Iberian Peninsula during the Late Republican period (2nd-1st c. BC) as indicators of Romanization (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyzes the presence of writing and registering instruments in several settlements of the NE Iberian Peninsula (2nd-1st c. BC), attempting to assess their historical, cultural and economic interest, as a reflection of the process of integration within the Roman world. It also analyzes the relation between these writing instruments and the local epigraphy.
Keywords: Stylus; Seal-boxes; Signaculum; Romanization